Pengaruh Membaca Al-Qur’an terhadap Prestasi Pembelajaran PAI Siswa SMP Al-Amin Kecamatan Pamijahan Kabupaten Bogor - Kamilah, Siti; Laelasari, Eda; Srihartini, Yusi (Ikatan Da'i Indonesia, 2023)
This research is motivated to investigate the influence student motivation to read the Al-Qur'an because of the class VII-1 SMP Al-Amin who can read the Al-Qur'an, but not motivated to apply it in a learning activity in PAI. Backgrounds are researchers interested in studying the student's ability to read the Al-Qur'an is to motivate learning Achievement PAI. This study aims to: (1) determine the ability to read the Al-Qur'an class VII-1 SMP Al-Amin, (2) find the motivation to read the Al-Qur'an to the learning Achievement PAI class VII-1 SMP Al-Amin, (3) the effect of motivation between the ability to read the Qur'an to the results of PAI class VII-1 SMP Al-Amin. This research is quantitative research with a conclusion through statistical analysis. Location of research on SMP Al-Amin Cibening Pamijahan the District of Bogor, with a population totaling 114 students. The sample in this study of 20 people with a stratified random sampling technique. This study uses a quantitative approach. The research instrument used a questionnaire to motivate reading the Al-Qur'an and the results of the report cards to determine student learning Achievement against the PAI lesson. Data analysis techniques include (1) test instruments, validity, and reliability. (2) Test prerequisites research, consisting of the analysis unit includes the value of Mean, Median, Mode, and standards of deviation. (3) Test the hypothesis, correlation test, reliability test, t test. Results: (1) There is a positive and significant influence student motivation Reading the Al-Qur'an to the results PAI of Class VII-1 SMP Al- Amin. Based on the results obtained by analysis of the price of the product- moment correlation coefficient rxy showed a strong/ positive value of 0.8504 while rtabel of 0.444 means rxy > rtabel. And reliability analysis results obtained r11 value indicates a positive value of 0.921 while rtabel of 0.444 means rhitung> rtabel, which means there is a relationship between motivation Student Reading the Al-Qur'an (X) with Learning Achievement PAI (Y). (2) Test the hypothesis result of motivation to read the Al-Qur'an thitung 10.038 while table = 2.101. thitung> ttabel (10.038> 2.101).